(untitled) (Acta Entomologica Serbica, 2010)
This paper deals with faunistical data and taxonomic notes on Odonata in Bosnia and Herzegovina. A database containing all available published, previously unpublished, and new data was made in order to create a review of the current knowledge of the country’s Odonata fauna and point out the priorities in future investigations. 57 Odonata species are listed as resident species in Bosnia and Herzegovina. Of that number, exact data on the occurrence of 6 species (Lestes parvidens, L. macrostigma, Erythromma viridulum, Aeshna grandis, Lindenia tetraphylla and Somatochlora flavomaculata) are presented and discussed here for the first time.